Impact of 13-Valent Pneumococcal Conjugate Vaccine on Pneumococcal Meningitis, Burkina Faso, 2016–2017. (31st October 2019) - Soeters, Heidi M; Kambiré, Dinanibè; Sawadogo, Guetawendé; Ouédraogo-Traoré, Rasmata; Bicaba, Brice; Medah, Isaïe; Sangaré, Lassana; Ouédraogo, Abdoul-Salam; Ouangraoua, Soumeya; Yaméogo, Issaka; Congo-Ouédraogo, Malika; Ky Ba, Absatou; et al.
Abstract: Background: In 2013, Burkina Faso introduced 13-valent pneumococcal conjugate vaccine (PCV13) into the routine childhood immunization program, to be administered to children at 8, 12, and 16 weeks of age. We evaluated the impact of PCV13 on pneumococcal meningitis. Methods: Using nationwide surveillance, we gathered demographic/clinical information and cerebrospinal fluid (CSF) results for meningitis cases. Pneumococcal cases were confirmed by culture, polymerase chain reaction (PCR), or latex agglutination; strains were serotyped using PCR. We compared annual incidence (cases per 100 000) 4 years after PCV13's introduction (2017) to average pre-PCV13 incidence (2011–2013). We adjusted incidence for age and proportion of cases with CSF tested at national laboratories. Results: In 2017, pneumococcal meningitis incidence was 2.7 overall and 10.5 (<1 year), 3.8 (1–4 years), 3.5 (5–14 years), and 1.4 (≥15 years) by age group. Compared to 2011–2013, PCV13-serotype incidence was significantly lower among all age groups, with the greatest decline among children aged <1 year (77%; 95% confidence interval [CI], 65%–84%). Among all ages, the drop in incidence was larger for PCV13 serotypes excluding serotype 1 (79%; 95% CI, 72%–84%) than for serotype 1 (52%; 95% CI, 44%–59%); incidence of non-PCV13 serotypes also declined (53%; 95% CI, 37%–65%). In 2017, 45% of serotyped cases among all ages were serotype 1 and 12% were other PCV13 serotypes. Conclusions: In Burkina Faso, meningitis caused by PCV13 serotypes continues to decrease, especially among young children. However, the concurrent decline in non-PCV13 serotypes and short pre-PCV13 observation period complicate evaluation of PCV13's impact. Efforts to improve control of serotype 1, such as switching from a 3 + 0 schedule to a 2 + 1 schedule, may improve overall control of pneumococcal meningitis in this setting.